(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: The contemporary workplace demands continuous learning, agility, and behavioral adaptability, shifting the foundations of what is traditionally understood as “talent.” While ability—encompassing skills, competencies, and domain expertise—remains an important predictor of performance, emerging organizational behavior research highlights attitude as the central catalyst influencing how ability is developed, applied, and sustained. This paper examines the attitude–ability nexus and explores how mindset, motivation, and emotional orientation reshape talent in dynamic work environments. Integrating psychological theories, behavioral frameworks, and empirical insights, the study proposes a conceptual model illustrating how attitude accelerates mastery by amplifying learning agility, adaptability, and interpersonal effectiveness. The paper concludes with implications for managers, HR practitioners, and researchers, emphasizing the critical need to prioritize attitudinal competencies in talent strategies.